The Health Enhancement of the Retirement Age based on Buddhism - Napikul, Supakorn; Visuddhimedhi, Phramaha Phongprabhakorn (ASEAN Journal of Religious and Cultural Research, 2022)
Most people's working lives begin between the ages of 18 and 59 and reach retirement at the age of 60. The retirement causes problems as many seniors after retirement experiencing changes whether it is a disease and a mental disease. Therefore, the preparation after retirement is an important issue that must be taken into account for the well-being of life after retirement. One of the ways that most seniors choose to practice is applying Buddhist principles for mind management. The Buddhist principles are as follows: 1) Three marks of existence, 2) Brahmavihara, 3) The world of drama, 4) Anapanasati and 5) Pratityasamutpada. The consequences of adhering to the principles of Buddhism leading to life will make the mind calmer and result in the elderly being healthier and be able to live happily in the society.